Impact of multivessel coronary artery disease on early and late clinical outcome in ST-Segment elevation myocardial infarction patients who underwent percutaneous coronary intervention: insight from Indonesia - Damarkusuma, Arditya; Taufiq, Nahar; Bagaswoto, Hendry Purnasidha; Saputra, Firandi; Sukmadja, Daniel; Setianto, Budi Yuli (Published by Universitas Gadjah Mada, 2024)
It is estimated that 15 people for every 1000 Indonesian residents suffer from cardiovascular disease (CVD) including ST-segment elevation myocardial infarction (STEMI). Percutaneous coronary intervention (PCI) is often performed in patients with STEMI. Several factors affect clinical outcome after PCI procedure including multivessel coronary artery disease. This study aimed to measure the impact of multivessel coronary artery disease on the early and late outcomes of STEMI patients undergoing PCI procedures. This was a prospective cohort study on STEMI patients undergoing PCI procedures from the period of August to December 2021. Two expected cohorts were performed i.e. patients who suffered from single-vessel disease (SVD) and patients who suffered from multivessel disease (MVD). Forty six patients with STEMI were enrolled in this study consisting of 24 (52.17%) patients with MVD and 22 (47.83%) patients with SVD. No significant difference in baseline characteristics between MVD and SVD groups was observed (p > 0.05). The MVD group (91.67%) used a more radial percutaneous approach compared with the SVD group (54.55%; p = 0.04). In addition, no significant difference between the SVD group and the MVD group in major adverse cardiovascular events (MACE) and echocardiographic outcome after 90-d follow up was observed (p > 0.05). In conclusion, MVD has similar impacts on early and late clinical outcomes compared with SVD in STEMI patients undergoing PCI procedures.